Christian Muslim relations : a bibliographical history. Volume 2, 900-1050 - Monferrer Sala, Juan Pedro.; Roggema, Barbara.; Thomas, David 1948- (The History of Christian-Muslim Relations, 2010)
Christian-Muslim Relations, a Bibliographical History 2 (CMR2) is the second part of a general history of relations between the faiths. Covering the period from 900 to 1050, it comprises a series of introductory essays, together with the main body of more than one hundred detailed entries on all the works by Christians and Muslims about and against one another that are known from this period. These entries provide biographical details of the authors where known, descriptions and assessments of the works themselves, and complete accounts of manuscripts, editions, translations and studies. The result of collaboration between leading scholars in the field, CMR2 is an indispensable basis for research in all elements of the history of Christian-Muslim relations.